The relationships between pregnancy-associated protein A levels, placental localization and fetal birth weight - A. E. Güler; M. Atasever; U. Fidan; E. Artürk; M. F. Kinci; S. Bodur (Акушерство, гинекология и репродукция, 2019)
Aim. This study was designed to determine the relationship between pregnancy-associated protein A (PAPP-A), placenta localization and fetal birth weight (FBW). Materials and methods. First trimester PAPP-A levels, second trimester placental localization and birth weights of 1145 infants were obtained through a retrospective review of the patient follow up charts in Koru Hospital. Serum PAPP-A levels were recorded as the multiple of median (MоM) values, the FBW values of infants were recorded in grams, and the placental localization was recorded under seven different pre-defined categories: 1. placenta anterior; 2. placenta posterior; 3. placenta fundal; 4. placenta fundal-anterior; 5. placenta fundal-posterior; 6. placenta lateral-right; 7. placenta lateral-left. The data were analyzed using the Statistical Package for Social Sciences (SPSS) program (SPSS Inc., Chicago, IL, USA). Results. There was no significant difference between the FBW and PAPP-A levels. The comparison of seven placental localizations shows that the anterior and posterior localizations have an impact on FBW of the infants. Conclusion. The FBW was highest in the cases where the placenta was located in the corpus uteri. We believe this finding is consistent with the fact that the corpus uteri receives the largest blood supply.